Export Competitiveness Indicators of the Fijian Sugar Industry - Shandil, Satya Nand (2005)
Competitiveness has always been a concern to most countries in recent years. The major problem, which is facing the Fijian sugar industry, is the decline in its share in the world market. This indicates that Fiji's export competitiveness in the world market is declining. The objective of this study is to examine the export competitiveness of the Fijian sugar industry by using selected indicators. The study utilises revealed comparative advantage (RCA), constant market-share (CMS) and shift-share technique to measure the competitiveness of the industry. The study uses secondary data collected from various sources, namely, the FAO, COMTRADE (ITC), UNCTAD, and FIBS and the analysis for this study is restricted to trade data from (1989 to 2003). The data is decomposed into three, five-year periods, i.e. Period I (from 1989-93), Period I1 (1 994-98) and Period I11 (1999-2003). The five-year periods is chosen because these periods coincide with the major policy changes, which are based on five-year development plan and political polices. The results obtained from the RCA computation indicates that Fiji has a comparative advantage in producing sugar. The performance of the industry for period 1989 to 1990 showed a comparative disadvantage, where RCA was less than one. However, it improved from 1991 but it showed a fluctuating trend in the performance. The RCA from 1992 onward was above one indicating comparative advantage. The Export Performance Ratio was 92.66 percent for period 1, 86.47 percent for period I1 and 70.10 percent for period 111. This indicates that Fiji's comparative advantage was declining over the study period. This happened because Fiji had to import sugar in period I1 and period 111 to maintain the requirements for preferential quota in EU market. Result of the Constant Market Share analysis shows that size of market is one of the dominating factors which determine the expansion of export of a country. In the case of Fiji, the opportunities exist for more export of sugar if Fiji has had maintained its market share of period I. However, the statistic revealed that Fiji's sugar production has declined and this subsequently has led to the decline in export. Fiji's sugar market competitiveness effect was negative between period I and 11. This was due to the reduction in Fiji's share in the world export market. If Fiji had maintained its share of period I, it would have an export market potential of 570,145 tonnes for period 111 (1999-2003), but it only exported 364,703 tonnes, resulting in a hypothetical loss of 205,442 tonnes. The fall in sugar production was due to a drop in cane production, which is attributed to non-renewal of agricultural land leases. The situation was further compounded by the adverse effect of climate such as drought and the hurricane. PERPUSTAKAAN SULTAN ,WUL SAMAD UNlVERSlTl PUTRA MA.IAYSIA Result of the shift share analysis indicates that the market opportun~t~eosf FIJI'S sugar are mainly offered by Indonesia, Malaysia, Korea, Canada, Singapore, China, New Zealand, and South Pacific Island States countries. In order to be competitive, the Fijian sugar industry needs to increase its share in the total export of Fiji. The competitiveness of the sugar industry was decreasing mainly due to the inability of the industry to maintain its sugar export share in world market due to the decrease in sugar production. Based on the above findings, and because sugar is a major contributor to the Fijian economy, it is imperative that the government rejuvenate the sugar industry by introducing several development programs and policies. These should include the followings: (i) integration of small farms into plantations, (ii) introduction of improved technology, (iii) making changes to in the payment system by giving emphasis on quality, (iv) provision of security to tenants, and (v) increase downstream activities.